Exploring Uranus. Issue 14 (8th April 2014) - Hofstadter, Mark; Lamy, Laurent
Abstract Ice giant planets such as Uranus have become a hot topic in the planetary and exoplanetary communities. This interest is driven by several factors, including the realization that these planets are fundamentally different from terrestrial and gas giant planets, the fact that they challenge current understanding of solar system formation and planetary evolution, and the new discovery that ice giants are abundant in our galaxy.